Development and validation of a tool for measuring digital library engagement - Rahimi Mohamad Rosman, Mohamad; Nasir Ismail, Mohd; Noorman Masrek, Mohamad (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Digital library engagement can be defined as the extensive usage of the services, functions, and tools provided by the digital library (DL). Although many instruments have been developed to measure digital library usage, however, the instruments were only measuring a limited aspect of usage, such as behavioral perspective. Therefore, the aim of this study is to establish and confirm a research instrument to measure digital library engagement. The study is conducted on several empirical phases. First, a listof variables was selected. Second, an instrument was developed based on the variables selected. Third, the instrument measuring digital library engagement was validated through expert review process. Fourth, face validity was conducted, before confirming the reliability of the instrument through a pilot test. Lastly, the instrument was validated through quantitative data collection by 492 respondents. As a result, a valid instrument consisting of 14 variables underneath 5 dimensions (technological, individual, contextual, digital library engagement, perceived benefits) and 61 items were produced. The instrument could be employed to identify and assess the state of digital library engagement among practitioners, universities, government, and local communities. This study however is limited in few ways in relation to context coverage, generalization of theory, and variables selection.